2008
DOI: 10.1002/chir.20659
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective single nucleotide polymorphism recogniton by a chiral (5S) PNA beacon

Abstract: A chiral peptide nucleic acid (PNA) beacon containing a C-5 modified monomer based on L-lysine was synthesized. The terminal amino group of the lysine side chain was linked to a spacer for future applications on surfaces. The PNA beacon bears a carboxyfluorescein fluorophore and a dabcyl quencher at opposite ends. The DNA binding properties were compared with those of a homologous PNA beacon containing only achiral monomers. Both beacons underwent a fluorescence increase in the presence of complementary DNA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…The use of modified PNA residues in PNA oligomers can also affect the binding affinity and selectivity to nucleic acids through backbone rigidification and preorganization [2527], increase solubility [28], provide a handle for further conjugation or ligand display [29] or increase cellular uptake [30]. Recent work with diethylene glycol γ-substituted PNA residues afforded oligomers that had both higher binding affinity to DNA and increased aqueous solubility [31].…”
Section: Pna As Dna Sequence-specific Targeting Drugsmentioning
confidence: 99%
“…The use of modified PNA residues in PNA oligomers can also affect the binding affinity and selectivity to nucleic acids through backbone rigidification and preorganization [2527], increase solubility [28], provide a handle for further conjugation or ligand display [29] or increase cellular uptake [30]. Recent work with diethylene glycol γ-substituted PNA residues afforded oligomers that had both higher binding affinity to DNA and increased aqueous solubility [31].…”
Section: Pna As Dna Sequence-specific Targeting Drugsmentioning
confidence: 99%
“…15,16,17 It was demonstrated by our group that g-PNA synthesized from Lamino acids were strong inducer of righthandedness of PNA:PNA duplexes;…”
mentioning
confidence: 99%
“…1 Recently, a number of modifications of the basic PNA monomeric units have been reported in order to improve the binding stability to the complementary nucleic acid and the specificity of complexation. [2][3][4][5] Among them, one of the most distinct modification is the introduction of stereogenic center at γ-carbon atom of the N-aminoethylglycine unit. 5 Compared to unmodified normal PNAs, the γ-substituted PNAs have several advantages of improved solubility, less self-aggregation, increased stability of PNA-DNA duplexes, and opportunities of further functionalization.…”
mentioning
confidence: 99%
“…[2][3][4][5] Among them, one of the most distinct modification is the introduction of stereogenic center at γ-carbon atom of the N-aminoethylglycine unit. 5 Compared to unmodified normal PNAs, the γ-substituted PNAs have several advantages of improved solubility, less self-aggregation, increased stability of PNA-DNA duplexes, and opportunities of further functionalization. 5,6 Also, it was reported that chiral PNAs have shown promising abilities in DNA recognition.…”
mentioning
confidence: 99%
See 1 more Smart Citation